Acute generalized exanthematous pustulosis in close temporal association with mRNA-1273 vaccine - Mitri, Fouad; Toberer, Ferdinand; Enk, Alexander; Hartmann, Martin (Acta dermato-venereologica, 2021)
Abstract is missing (Short communication)